Estimating the Parameters of Traffic Flows on the Basis of Processing of Localization Data on the Movement of Vehicles - Denis Kapski; Valery Kasyanik; Oleksii Lobashov; Aleksandra Volynets; Oleg Kaptsevich; Andrii Galkin (Communications - Scientific letters of the University of Zilina, 2019)
The article describes the method of estimating the parameters of transport flows using the two-fluid mathematical model of Herman-Prigogine and developed and based on the proposed method of estimating the parameters of the system on the basis of passive processing of navigation data on the movement of vehicles. The efficiency of the proposed algorithms, mathematical models for estimating the parameters of road traffic flow and system as a whole was confirmed during its testing using a set of tracks on the main highways of Commonwealth of Independent States.